Analisis Hukum Terhadap Pencegahan Kasus Deepfake Serta Perlindungan Hukum Terhadap Korban - Respati, Adnasohn Aqilla; Setyarini, Astri Dewi; Parlagutan, Dodi; Rafli, Muhammad; Mahendra, Rayhan Syahbana; Nugroho, Andriyanto Adhi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research will examine various legal aspects related to Deepfake Porn, including the role of law in protecting individual privacy, copyright, and cyber security. In addition, this research will also explore the potential for public awareness education as a preventative measure by increasing public understanding of the risks of Deepfakes and how to protect themselves from possible misuse of this technology. The research method that can be used to analyze efforts to prevent deepfake pornography and educate public awareness in the digital environment is the normative juridical research method. The steps in this method include identifying the legal problem to be researched, collecting data through searching regulations and literature related to the problem. Protection of personal data in the use of Artificial Intelligence (AI) technology is very important to avoid threats such as deepfake videos. Personal data, including personal photos, must be legally protected. Privacy is divided into three types: Physical Privacy, Information Privacy, and Organizational Privacy, which includes protection of individual communications, behavior and identity. In Europe, citizens can exercise the